Loss of β‐Actin Leads to Accelerated Mineralization and Dysregulation of Osteoblast‐Differentiation Genes during Osteogenic Reprogramming. Issue 23 (27th October 2020) - Gjorgjieva, Tamara; Xie, Xin; Commins, Patrick; Pasricha, Renu; Mahmood, Syed Raza; Gunsalus, Kristin C.; Naumov, Panče; Percipalle, Piergiorgio
Abstract: Actin plays fundamental roles in both the cytoplasm and the cell nucleus. In the nucleus, β ‐actin regulates neuronal reprogramming by consolidating a heterochromatin landscape required for transcription of neuronal gene programs, yet it remains unknown whether it has a role in other differentiation models. To explore the potential roles of β ‐actin in osteogenesis, β ‐actin wild‐type (WT) and β ‐actin knockout (KO) mouse embryonic fibroblasts (MEFs) are reprogrammed to osteoblast‐like cells using small molecules in vitro. It is discovered that loss of β ‐actin leads to an accelerated mineralization phenotype (hypermineralization), accompanied with enhanced formation of extracellular hydroxyapatite microcrystals, which originate in the mitochondria in the form of microgranules. This phenotype is a consequence of rapid upregulation of mitochondrial genes including those involved in oxidative phosphorylation (OXPHOS) in reprogrammed KO cells. It is further found that osteogenic gene programs are differentially regulated between WT and KO cells, with clusters of genes exhibiting different temporal expression patterns. A novel function for β ‐actin in osteogenic reprogramming through a mitochondria‐based mechanism that controls cell‐mediated mineralization is proposed. Abstract : The present study highlights a new function for β ‐actin in transcriptional reprograming during osteogenic differentiation, leading to cell‐mediated mineralization. β ‐actin performs this task by regulating expression of osteogenic factors and mitochondrial genes during osteogenesis. These observations support the novel involvement of cytoskeletal proteins such as actin in gene expression regulation during development and differentiation.